The effects of glucose and insulin on renal electrolyte transport. - DeFronzo, R A (1976)
The effects of hyperglycemia and hyperinsulinemia on renal handling of sodium, calcium, and phosphate were studied in dogs employing the recollection micropuncture technique. Subthreshold sustained hyperglycemia resulted in an isonatric inhibition of proximal tubular sodium, fluid, calcium, and phosphate reabsorption by 8-14%. Fractional excretion of sodium and phosphate, however, fell (P is less than 0.01) indicating that the increased delivery of these ions was reabsorbed in portions of the nephron distal to the site of puncture and in addition net sodium and phosphate transport was enhanced resulting in a significant antinatriuresis and antiphosphaturia. The creation of a steady state plateau of hyperinsulinemia while maintaining the blood glucose concentration of euglycemic levels mimicked the effects of hyperglycemia on proximal tubular transport and fractional excretion of sodium and calcium. Tubular fluid to plasma insulin ratio fell, similar to the hyperglycemic studies. These results suggest that the effects of hyperglycemia on renal handling of sodium and calcium may be mediated through changes in plasma insulin concentration. In contrast to hyperglycemia, however, hyperinsulinemia cuased a significant fall in tubular fluid to plasma phosphate ratio with enhanced proximal tubular phosphate reabsorption (P is less than 0.02). This occurred concomitantly with a significant inhibition of proximal tubular sodium transport. These data indicate that insulin has a direct effect on proximal tubular phosphate reabsorption, and this effect of insulin is masked by the presence of increased amounts of unreabsorbed glucose in the tubule that ensues when hyperinsulinemia occurs secondary to hyperglycemia. Fractional excretion of phosphate fell significantly during insulin infusion but unlike the hyperglycemic studies, the fall in phosphate excretion could be entirely accounted for by enhanced proximal reabsorption.